2018
DOI: 10.1111/cas.13624
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type I induces EGFRTKI resistance in EGFR‐mutated cancer cells by mTOR activation through Akt‐independent pathway

Abstract: Primary resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) is a serious problem in lung adenocarcinoma patients harboring EGFR mutations. The aim of this study was to examine whether and how collagen type I (Col I), the most abundantly deposited matrix in tumor stroma, affects EGFR‐TKI sensitivity in EGFR‐mutant cells. We evaluated the EGFR‐TKI sensitivity of EGFR‐mutated cancer cells cultured with Col I. Changes in the activation of downstream signaling molecules of EGFR wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…In addition, increased COLI did not alter primary tumor growth and ERα expression but enhanced circulating cancer cells and metastasizing cancer cells with decreased phospho-STAT5 expression, increased phospho-ERK1/2, and increased phospho-AKT expression; this phenomenon coincided with the formation of invasive protrusions of the primary tumor harboring collagen fibers angled perpendicularly to the tumor mass [75]. However, COLI in non-small cell lung cancer (NSCLC) induced mTOR activation through an AKT-independent pathway, leading to EGFR-tyrosine kinase inhibitor resistance [76]. The Notch3-COL4A2 loop promoted anoikis resistance with a reduction in phosphorylated AKT and ERK 1/2 in ovarian cancer cells [77].…”
Section: The Influence Of Collagen On Cancer Cell Behaviormentioning
confidence: 99%
“…In addition, increased COLI did not alter primary tumor growth and ERα expression but enhanced circulating cancer cells and metastasizing cancer cells with decreased phospho-STAT5 expression, increased phospho-ERK1/2, and increased phospho-AKT expression; this phenomenon coincided with the formation of invasive protrusions of the primary tumor harboring collagen fibers angled perpendicularly to the tumor mass [75]. However, COLI in non-small cell lung cancer (NSCLC) induced mTOR activation through an AKT-independent pathway, leading to EGFR-tyrosine kinase inhibitor resistance [76]. The Notch3-COL4A2 loop promoted anoikis resistance with a reduction in phosphorylated AKT and ERK 1/2 in ovarian cancer cells [77].…”
Section: The Influence Of Collagen On Cancer Cell Behaviormentioning
confidence: 99%
“…However, PD-(L)1 blockade in KP GEM mice showed only transient effects, without a long-term reduction in primary lung tumor growth or improvement in animal survival 8 . In addition to high PD-L1 expression, our prior work also demonstrated that KP lung tumors have increased LOXL2 crosslinking, which stabilizes and enhances the deposition of collagen, a main component of the ECM that has been implicated in promoting lung tumor progression, metastasis and drug resistance [14][15][16][17] . Furthermore, studies have also correlated TGF-β signaling and TGF-βassociated ECM gene signatures, such as collagen, with tumor immune suppression and anti-PD-1/PD-L1 resistance 18,19 .…”
mentioning
confidence: 91%
“…In nonsmall cell lung cancer, high stroma‐tumor ratios (≥50% stroma) correlate with decreased survival . Culture of cells from LUAD diagnosed patients showed that the presence of collagen type 1, a main protein deposited in fibrosis, resulted in significantly shorter progression‐free survival time after therapy . Since cancer‐related mortality is due to tumor cell metastasis, which is driven by tumor‐associated fibroblasts and fibrosis, approaches to mitigate fibrotic initiation in the setting of solid tumors could reduce metastasis and improve survival.…”
Section: Introductionmentioning
confidence: 99%